Diagnosing and Treating Chronic Pain: Are We Doing This Right?. (April 2021) - Carnago, Lisa; O'Regan, Amy; Hughes, Jaime M.
The diagnosis, treatment, and management of chronic pain is complex, nuanced, and challenging in primary care settings. These challenges often give rise to internal provider conflicts around appropriate management strategies, perhaps avoiding diagnosis all together. Factors that contribute to internal provider conflict include knowledge, responsibility, and uncertainties surrounding chronic pain management. This piece acknowledges the complexity and competing priorities of chronic pain management from a provider perspective. We advocate for coordinated and committed care of patients with chronic pain and a sense of shared responsibility among providers to adequately address patient needs.